Artificial Defects in 316L Stainless Steel Produced by Laser Powder Bed Fusion: Printability, Microstructure, and Effects on the Very‐High‐Cycle Fatigue Behavior. Issue 1 (25th October 2022) - Voloskov, Boris; Mishurova, Tatiana; Evlashin, Stanislav; Akhatov, Iskander; Bruno, Giovanni; Sergeichev, Ivan
Abstract : The printability of artificial defects inside the additively manufactured laser powder bed fusion (LPBF) 316L stainless steel is investigated. The printing parameters of the LPBF process are optimized to produce artificial defects with reproducible sizes at desired positions while minimizing redundant porosity. The smallest obtained artificial defect is 90 μm in diameter. The accuracy of the geometry of the printed defect depends on both the height and the diameter in the input model. The effect of artificial defects on the very‐high‐cycle fatigue (VHCF) behavior of LPBF 316L stainless steel is also studied. The specimens printed with artificial defects in the center are tested under VHCF using an ultrasonic machine. Crack initiation is accompanied by the formation of a fine granular area (FGA), typical of VHCF. Despite the presence of relatively large artificial defects, FGA formation is observed around accidental natural printing defects closer to the surface, which can still be considered as internal. The causes for this occurrence are discussed. Abstract : The printability of artificial defects in additively manufactured laser powder bed fusion (LPBF) 316L stainless steel is investigated. The printing parameters of the process are optimized to produce defects with reproducible sizes at desired positions while minimizing porosity. The effect of artificial defects on the material's very‐high‐cycle fatigue (VHCF) behavior is also studied.